Do citation systems represent theories of truth? - Betsy Van der Veer Martens (Information Research: An International Electronic Journal)
This article suggests that the citation can be viewed not only as a "concept symbol" but also as a "boundary object". The scientific, legal, and patent citation systems in America are examined at the micro, meso, and macro levels in order to understand how they function as commodified theories of truth in contemporary knowledge representation. This approach also offers a meta-theoretical overview of existing citation research efforts in science, law, and technology that may be of interdisciplinary interest.